Satisfacción laboral y su influencia en la productividad en las Mipymes de la provincia de El Oro. - Ortiz Ajila, Bryan Leonidas; Lavayen Chalaco, Rosa Katherine (Universidad Técnica de Machala, 2022)
The objective of this integrative project is to evaluate the influence of job satisfaction on the productivity of MSMEs in the province of El Oro, in which different subtopics were addressed that helped to better understand the subject. In this research work, the population includes all the MSMEs established or identified in the province of El Oro by Supercias, with a total population of 2,593 registered companies, of which this data was considered as the total population. The sample consisted of 285 responses obtained from collaborators from different entities, to whom a survey consisting of 19 questions related to indicators of job satisfaction and productivity was applied; the same questions are divided by section, in the case of job satisfaction, the indicators are: Expectation, instrumentality, valence, likewise the indicators to measure productivity were: Efficiency, effectiveness, adaptability. The present study obeys the non-Experimental - cross-sectional research design, because the variables are not manipulated, only historical information is analyzed, the effects caused by the variables are observed and analyzed. It is cross-sectional because data was collected in a single time. The research approach is also quantitative, because numerical data was used that allows the variables to be related. The data from the surveys were processed in the statistical program IBM SPSS to find the correlation between the variables, where the results obtained indicated that there is a positive correlation with a Pearson coefficient of 0.885. As a consequence, the null hypothesis "Ho" is rejected and the alternative hypothesis "H1" is accepted, which indicates that there is a correlation between the variables job satisfaction and productivity.
El presente proyecto integrador tiene como objetivo evaluar la influencia de la satisfacción laboral en la productividad de las MIPYMES de la provincia de El Oro, en el cual se abordaron distintos subtemas que ayudaron a un mejor entendimiento del tema. En este trabajo de investigación la población comprende a todas las MIPYMES establecidas o identificadas en la provincia de El Oro por la Superintendencia de compañías, valores y seguros, con una población total de 2593 empresas registradas, de lo cual se consideró a este dato como la población total. La muestra estuvo compuesta por 285 respuestas obtenidas de colaboradores de diferentes entidades, a los mismos se les aplico una encuesta conformada por 19 preguntas relacionadas a los indicadores de satisfacción laboral y productividad; las mismas interrogantes se encuentran divididas por sección, en el caso de la satisfacción laboral, los indicadores son: Expectativa, instrumentalidad, valencia, así mismo los indicadores para medir la productividad fueron: Eficiencia, eficacia, adaptabilidad. El presente estudio obedece al diseño de investigación no Experimental – transversal, debido a que no se manipulan las variables, solo se analiza información histórica, se observan y analizan los efectos que provocan las variables. Es transversal debido a que se recolecto datos en un único tiempo. El enfoque de la investigación también es cuantitativo, porque se utilizó datos numéricos que permiten relacionar las variables. Los datos de las encuestas fueron procesados en el programa estadístico IBM SPSS para encontrar la correlación existente entre las variables, donde los resultados obtenidos indicaron que existe una correlación positiva con un coeficiente de Pearson del 0,885. Como consecuencia se rechaza la hipótesis nula “Ho” y se acepta la hipótesis alternativa “H1” que nos indica que si existe correlación entre las variables satisfacción laboral y productividad.
Keywords: SATISFACCION LABORAL; PRODUCTIVIDAD; COLABORADORES; MIPYMES